Structural variations of photosystem I-antenna supercomplex in response to adaptations to different light environments - Suga, Michihiro; Shen, Jian-Ren (Current opinion in structural biology, 2020)
Photosystem I (PSI) is one of the two photosystems in photosynthesis, and generates reducing power required for carbon dioxide fixation. PSI exists as a reaction center core in cyanobacteria but is surrounded by light-harvesting antenna complexes (LHCI) to form PSI-LHCI supercomplexes in eukaryotic organisms. The structures of PSI core and PSI-LHCI have been reported from various organisms. We compare these structures and highlight the differences among different organisms. While the PSI core is more conserved, there are differences in its subunit composition and organization. Larger differences are found in the subunit composition, organization, and pigment binding in LHCI. All these changes can be explained in the framework of better adaptation to different light environment that each photosynthetic organism inhabits.